FOSTERING FIRST LANGUAGE SKILLS THROUGH EARLY LISTENING ACTIVITIES: A CASE STUDY ON A PRE-SCHOOL CHILD’S LANGUAGE ACQUISITION - Wahyuni, Irma (Research And Innovation In Language Learning (RILL), 2020)
Language skills acquisition in children indicates a remarkable achievement for every parent as the ability of comprehending and producing the language is one of the most important basic skills in human?s development. Approaching the age of five, a normal child?s language development is in a complex-linguistic period where she is able to produce a language with a firm grammatical structure as adults conduct. Interestingly, this happened without a regular and structured grammar learning process. However, some factors play significant roles to activating cognitive systems in children (Wahyuni, 2019) which stimulates their language skills. The most basic language skill in children that is able to be fostered early is listening skill which they have needed and acquired before they reach their first year of age and will be continuously developed during their language development journey. Listening becomes crucial for them as it cognitively creates a comprehensible input before creating outputs for them to producing the language, before they start speaking. Applying an intrinsic case study on a pre-school (near five-year old) child, this qualitative research tries to describe how the process of early listening skill can be trained by parents or care-givers to stimulate children?s language skills acquisition in their first language (L1) skills acquisition. Specifically it sheds some light on how early listening skill foster L1 skill in children. Some suggestions regarding improvement strategies related to establishing early listening skills in children are presented as well as additional implication of this study for future researches.